A novel MAs(III)-selective ArsR transcriptional repressor - Chen, Jian (Mol Microbiol, 2017)
Microbial expression of genes for resistance to heavy metals and metalloids is usually transcriptionally regulated by the toxic ions themselves. Arsenic is a ubiquitous, naturally occurring toxic metalloid widely distributed in soil and groundwater. Microbes biotransform both arsenate (As(V)) and arsenite (As(III)) into more toxic methylated metabolites methylarsenite (MAs(III)) and dimethylarsenite (DMAs(III)). Environmental arsenic is sensed by members of the ArsR/SmtB family. The arsR gene is autoregulated and is typically part of an operon that contains other ars genes involved in arsenic detoxification. To date every identified ArsR is regulated by inorganic As(III). Here we described a novel ArsR from Shewanella putrefaciens selective for MAs(III). SpArsR orthologs control expression of two MAs(III) resistance genes, arsP that encodes the ArsP MAs(III) efflux permease, and arsH encoding the ArsH MAs(III) oxidase. SpArsR has two conversed cysteine residues, Cys101 and Cys102. Mutation of either resulted in loss of MAs(III) binding, indicating that they form an MAs(III) binding site. SpArsR can be converted into an As(III)-responsive repressor by introduction of an additional cysteine that allows for 3-coordinate As(III) binding. Our results indicate that SpArsR evolved selectivity for MAs(III) over As(III) in order to control expression of genes for MAs(III) detoxification.